Strengthening National Economic Fundamentals for ASEAN SDGs 2025 from the Islamic Economic Perspectives - Anton Bawono (Postgraduate Program, Universitas Islam Negeri (UIN) K. H. Abdurrahman Wahid Pekalongan, Indonesia, 2019)
Data and observations in the field showed that Indonesia was rich in human and natural resources. On the other hand, Indonesia is currently quite dependent on foreign products which makes this nation vulnerable to global changes whereas economic stability is indispensable for the achievement of planned economic growth. Therefore, a sustainable development strategy is needed in line with ASEAN SDGs 2025 as a solution to strengthening national economic fundamentals. The purpose of this research is the first, to analyze and observe how far the endowment factors that Indonesia has in terms of availability and sustainability. Second, find the best solution for the strengthening of national economic fundamentals from the perspective of Islamic economics. The research method used is SWOT analysis from endowment factors owned by Indonesia, domestic and foreign markets, solutions to a strengthening of national economic fundamentals in an Islamic economic perspective. The SWOT analysis conducted did not end in the qualitative analysis but also continued with a quantitative SWOT analysis. The results of the analysis show that the Indonesian nation has endowment factors in the form of human resources and natural resources while the combination strategy should use the SO strategy because it has the highest score and the analysis results on the IE matrix got the coordinates (positive: positive) entered quadrant I (supporting the aggressive strategy).